Peranan Guru Dalam Pelaksanaan Program Gerkan Literasi Sebagai Upaya Pembentukan Civic Knowledge - Nurlaila Hafizd Hakiki; Berchah Pitoewas; Abdul Halim (FKIP Unila, 2019)
The purpose of this study is to explain the teacher’s roles in the literacy movement program as a forming efforts of civic knowledge in SMP Negeri 2 Metro academic year 2018/2019. This study used a descriptive method with a quantitative approach. The populations is 737 students. The sample in this study was taken a smuchas 10% thus the total number of 74 students. Data collection techniques applied are questionnaires and documentation. Data analysis techniques applied are the percentage formula and chi squared. The result of this study shows that teacher’s roles in the implementation of literacy movement program as a forming efforts of Civic Knowledge in SMP Negeri 2 Metro academic year 2018/2019 included as a good category the teachers have done their roles in the implementation of literacy at school, So that through Civic Knowledge literacy students can be well formed. Thus, the teacher’s roles in the implementation of literacy movement program in SMP Negeri 2 Metro can be said goes well.Tujuan Penelitian ini untuk menjelaskan peranan guru dalam pelaksanaan program gerakan literasi sebagai upaya pembentukan civic knowledge di SMP Negeri 2 Metro Tahun Pelajaran 2018/2019. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Jumlah populasi sebanyak 737 peserta didik. Sampel dalam penelitian ini diambil sebanyak 10% dengan demikian jumlah keseluruhan 74 peserta didik. Teknik pengumpulan data menggunakan angket dan dokumentasi. Teknik analisi data menggunakan rumus persentase dan Chi kuadrat. Hasil penelitian ini menunjukkan bahwa peranan guru dalam pelaksanaan program gerakan literasi sebagai upaya pembentukan civic knowledge di SMP Negeri 2 Metro Tahun Pelajaran 2018/2019 masuk dalam kategori baik, guru telah menjalankan peranannya dalam pelaksanaan literasi di sekolah sehingga melalui literasi civic knowledge peserta didik dapat terbentuk dengan baik. Artinya peran guru dalam pelaksanaan program gerakan literasi di SMP Negeri 2 Metro dapat dikatakan berperan dengan baik.Kata Kunci: peran guru, literasi, civic knowledge